Voicing the Unspeakable: Indian Daughters Writing Mothers - Sarkar, D.T.S.S College of Commerce, Mumbai, India, Sucharita (Asiatic: IIUM Journal of English Language and Literature, 2016)
Indian society has traditionally glorified the mother as the silent and submissive producer of sons. In the context of hegemonic patriarchal discourse, the motherdaughter relationship has been an â€œunspeakable plotâ€ (Hirsch 1). Yet mothers have always shaped their daughtersâ€™ identities through their own sacrifices and resistances. In this paper, I have examined the contours of the mother-daughter plot through two texts by Indian daughters/writers: Mai: A Novel by Geetanjali Shree (1997; translated from Hindi by Nita Kumar, 2000), and the â€œbiography-novelâ€ Diddi: My Motherâ€™s Voice by Ira Pande (2005). Although both texts are located in middle class, upper caste families in North India, the mothers respond to patriarchal subjugation in contrasting ways. These texts challenge and subvert patriarchy at various levels: by reasserting the centrality of the mother-daughter relationship; by narrating stories of maternal resistances within and outside the family; by articulating the ambivalences felt by daughters and their consciousness of progressive empowerment; by examining the problematic relationship between procreativity and creativity; by unpacking the social construct of motherhood through the prism of the daughtersâ€™ representations; and by tracing the formation of the â€œmotherlineâ€ (Lowinsky 1) which creates, values and transmits enabling maternal legacies. Using the methodologies of comparative textual analysis and feminist psychoanalysis, I have attempted to rediscover the â€œmatronymicâ€ that is â€œblanked out by the patronymicâ€ in the family plot (Gilbert and Gubar 378) as narrated by daughters writing their mothers in India.